Aleksander Cheishvili in Emigration - Avtandil Nikoleishvili (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2011)
In the period of Aleksandre Cheishvili's (1903-1962) life and activity in Georgia, his novel "Lego" (1938) became the most significant specimen of his literary legacy. In it the process of establishment of collective farming in the countryside was reflected with tendentiousness widely charasteristic of Georgian literature of the Soviet period. However, "Leo" was not an exception, and the main purpose of the majority of Cheishvili's literary works lay in the laudation of the reality of the period. The government of the time appreciated Cheishvili's loyal service, showering him with honors. Bearing this in mind, it is hard to explain what made him leave his family and become an emigrant. As is known, in 1958 the writer crossed into West Germany and asked for political asylum there. In the opinion of a large part of Georgian society, Cheishvili was sent to Germany by the Soviet intelligence service. The validity of this view is confirmed by the letters sent by the writer in emigration to members of his family and various officials, without any restrictions. Apart from the cited material, search for his manuscripts in Germany and bringing them to Georgia will be extremely significant for an in-depth study of Cheishvili's emigre life. They will help to form a clearer idea of the real circumstances that determined his going into exile and the German period of his life.